2001
DOI: 10.1128/jb.183.1.36-45.2001
|View full text |Cite
|
Sign up to set email alerts
|

The chvH Locus of Agrobacterium Encodes a Homologue of an Elongation Factor Involved in Protein Synthesis

Abstract: The virulence of Agrobacterium tumefaciens depends on both chromosome-and Ti plasmid-encoded gene products. In this study, we characterize a chromosomal locus, chvH, previously identified by TnphoA mutagenesis and shown to be required for tumor formation. Through DNA sequencing and comparison of the sequence with identified sequences in the database, we show that this locus encodes a protein similar in sequence to elongation factor P, a protein thought to be involved in peptide bond synthesis in Escherichia co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 53 publications
(40 reference statements)
2
43
0
Order By: Relevance
“…These findings were corroborated by a recent study which reported changes of equally small magnitudes in the soluble proteome of an E. coli efp mutant (60). This finding is also consistent with data obtained for the efp (chvH) mutant of Agrobacterium tumefaciens, where few differences were observed in the protein profiles of the mutant and wild-type strains using one-dimensional SDS-PAGE, except for a single, unidentified 32-kDa protein that was expressed at much higher levels in the mutant (47).…”
Section: Figsupporting
confidence: 80%
See 2 more Smart Citations
“…These findings were corroborated by a recent study which reported changes of equally small magnitudes in the soluble proteome of an E. coli efp mutant (60). This finding is also consistent with data obtained for the efp (chvH) mutant of Agrobacterium tumefaciens, where few differences were observed in the protein profiles of the mutant and wild-type strains using one-dimensional SDS-PAGE, except for a single, unidentified 32-kDa protein that was expressed at much higher levels in the mutant (47).…”
Section: Figsupporting
confidence: 80%
“…It is possible that a difference in strain background or growth condition, such as high temperature or low-osmolarity medium, led to the earlier conclusion that this factor is essential. In addition to Salmonella, EF-P has been successfully knocked out in E. coli, Agrobacterium, and Acinetobacter (5,17,47,59). In the case of the Acinetobacter efp mutant, suppressor mutations conveying enhanced growth were obtained after a few generations (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasmid pE43 carried the Pseudomonas aeruginosa strain 142 ohb genes cloned into the broad-host-range vector pSP329, carrying a multiple cloning site and lacZ a-complementation fragment cloned into the HaeII site of the plasmid pTJS75, a derivative of R-factor RK2 [5].…”
Section: Pcb-degrading Ohb Genes and Procedures For Electroporationmentioning
confidence: 99%
“…Properly modified EF-P is necessary for the virulence of several bacterial species, including Salmonella enterica and Agrobacterium tumefaciens (29,30). Here we investigate the role of EF-P and its modification in the virulence of S. flexneri.…”
mentioning
confidence: 99%